2006
DOI: 10.1002/med.20073
|View full text |Cite
|
Sign up to set email alerts
|

Intervention strategies to inhibit protein carbonylation by lipoxidation‐derived reactive carbonyls

Abstract: Protein carbonylation induced by reactive carbonyl species (RCS) generated by peroxidation of polyunsaturated fatty acids plays a significant role in the etiology and/or progression of several human diseases, such as cardiovascular (e.g., atherosclerosis, long-term complications of diabetes) and neurodegenerative diseases (e.g., Alzheimer's disease, Parkinson's disease, and cerebral ischemia). Most of the biological effects of intermediate RCS, mainly alpha,beta-unsaturated aldehydes, di-aldehydes, and keto-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
241
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(248 citation statements)
references
References 292 publications
(300 reference statements)
2
241
2
3
Order By: Relevance
“…Experimental studies indicated that carnosine plays an important role as anti-aging molecule. 52 Carnosine also stimulates the enzyme calcium ATPase and the calcium pump. This is important because the transmission of nerve impulses depends on calcium.…”
Section: Sources Of Endogenous Reactive Substancesmentioning
confidence: 99%
“…Experimental studies indicated that carnosine plays an important role as anti-aging molecule. 52 Carnosine also stimulates the enzyme calcium ATPase and the calcium pump. This is important because the transmission of nerve impulses depends on calcium.…”
Section: Sources Of Endogenous Reactive Substancesmentioning
confidence: 99%
“…In recent years, methods based on chemiluminescence and fluorescence measurements have been widely used for determination of ROS, RNS and lipid peroxidation metabolites. Fluorescent protein adducts are derivatives formed by reaction of secondary metabolites of lipid peroxidation (especially HNE and MDA) with free amino groups of proteins (Aldini et al, 2007;Requena et al, 1996). In murine and human serum, albumin protein fraction was identified as the most fluorescent fraction of proteins (Tsuchida et al, 1985).…”
Section: Adjuvant Arthritis: An Animal Model For Preclinical Evaluatimentioning
confidence: 99%
“…Different stages of RCS, ALE and AGE formation and AGE-mediated damage are suggested as therapeutic intervention strategies (Peyroux and Sternberg, 2006;Aldini et al, 2007;Peng et al, 2011). Peyroux and Sternberg (2006) classified these strategies as follows: (i) trapping of reactive dicarbonyl species, (ii) AGE cross-link cleavage, (iii) AGE receptor blocking, (iv) AGE receptor signalling blocking, (v) glycemia reduction by antidiabetic therapy, (vi) aldose reductase inhibition; (vii) shunting of trioses-phosphate toward the pentose-phosphate pathway by transketolase activation; (viii) antioxidant therapy by transition metal chelation and free radical scavenging.…”
Section: Therapeutic Strategies To Fight Against Carbonyl/oxidative Smentioning
confidence: 99%